THE IMPORTANCE OF PERMANENT LEARNING IN SPORT (Heritage, 2020)
The development of self-educational competence of employees is of key importance in the modern way of doing business. Therefore, it is very important that employees are trained for self-education, so that it does not take place spontaneously and at the free discretion of the individual. Therefore, the paper pays special attention to the analysis of educational needs as a starting point for employee training. The paper also talks about the professional development of employees, its importance for career development, but also the organization as a whole. The aim of this paper is to point out the importance of self - education of employees in sports, and to give a review of the reviewed literature in this field-
Keywords: self-education, lifelong learning, individual training